The Phys-Can study: meaningful and challenging - supervising physical exercise in a community-based setting for persons undergoing curative oncological treatment. (2nd January 2022) - Henriksson, Anna; Igelström, Helena; Arving, Cecilia; Nordin, Karin; Johansson, Birgitta; Demmelmaier, Ingrid
ABSTRACT: Introduction : Supervised exercise may improve physical function and quality of life during oncological treatment. Providing supervised exercise to all patients at hospitals may be impractical, with community-based settings (e.g. public gyms) as a possible alternative. To facilitate implementation, knowledge about the experiences of professionals who deliver exercise programs in community-based settings is crucial. Objective : To explore how physical therapists and personal trainers experience supervising exercise in a community-based setting for persons undergoing curative oncological treatment. Methods : Nine physical therapists and two personal trainers (coaches) were interviewed individually. The semi-structured interviews lasted 33–67 minutes and were analyzed using thematic analysis. Results : Two main themes emerged: "A meaningful task" and "A challenging task, " with nine sub-themes. The coaches experienced supervising exercise for persons undergoing treatment as meaningful, as they became a link between oncology care and health promotion. They grew more confident in the role and ascertained that exercising during treatment was feasible. Challenges included managing side effects of treatment and contradictory information from oncology care staff at hospitals, advising patients not to exercise. Conclusion : Supervising exercise for persons undergoing oncological treatment in a community-based setting may be highly rewarding for professionals who deliver exercise programs, which is promising for implementation. However, patients receive contradictory information about exercise, which may prevent physical activity. Also, supervising exercise for persons undergoing oncological treatment requires skills training; this is suggested for inclusion in educational programs for physical therapists and others. Future research should focus on strategies for cooperation between oncology care and health promotion.